Transcriptional regulator-mediated activation of adaptation genes triggers CRISPR de novo spacer acquisition - Liu, Tao; Li, Yingjun; Wang, Xiaodi; Ye, Qing; Li, Huan; Liang, Yunxiang; She, Qunxin; Peng, Nan (Nucleic acids research, 2015)
Acquisition of de novo spacer sequences confers CRISPR-Cas with a memory to defend against invading genetic elements. However, the mechanism of regulation of CRISPR spacer acquisition remains unknown. Here we examine the transcriptional regulation of the conserved spacer acquisition genes in Type I-A of Sulfolobus islandicus REY15A. Csa3a, a MarR-like transcription factor encoded by the gene located adjacent to csa1, cas1, cas2 and cas4 cluster, but on the reverse strand, was demonstrated to specifically bind to the csa1 and cas1 promoters with the imperfect palindromic sequence. Importantly, it was demonstrated that the transcription level of csa1, cas1, cas2 and cas4 was significantly enhanced in a csa3a-overexpression strain and, moreover, the Csa1 and Cas1 protein levels were increased in this strain. Furthermore, we demonstrated the hyperactive uptake of unique spacers within both CRISPR loci in the presence of the csa3a overexpression vector. The spacer acquisition process is dependent on the CCN PAM sequence and protospacer selection is random and non-directional. These results suggested a regulation mechanism of CRISPR spacer acquisition where a single transcriptional regulator senses the presence of an invading element and then activates spacer acquisition gene expression which leads to de novo spacer uptake from the invading element.